A portrait of a contemporary economic migrant from Ukraine in Poland - Pierkova, Daria (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
The goal of the article is to characterize economic migrants from Ukraine working in Poland and the problems they encounter during their stay. The introduction of the article is characterized in the introduction. Then, the methodological aspects of own research and the obtained results were discussed. The final fragment presents the conclusions of the research - a portrait of a labor migrant from Ukraine working in Poland. The research was conducted among 305 employees from Ukraine aged 18-65 who have experience of working in Poland. Ukrainian labor migrants have become an inseparable element of the Polish labor market. By getting to know them, we can create better conditions for their stay and employment in Poland.